PEMANFAATAN INSTAGRAM @MADIUNUMBULSQUARE SEBAGAI MEDIA PROMOSI DALAM MENINGKATKAN MINAT PENGUNJUNG TAMAN WISATA MADIUN UMBUL SQUARE - ahmad bustan sukron mubaroq; Andhita Risko Faristiana (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
The use of Instagram social media is used by the community in carrying out many activities ranging from entertainment, doing business, looking for information or other activities. This study examines and discusses how Instagram is used as a promotional medium by the Madiun Umbul Square tourist park which is managed by the Marketing and Creative team through the Instagram account @maduiunumbulsquare and to find out follower responses to posts on the Instagram account @madiunumbulsquare. This research uses a descriptive qualitative method by collecting data through interviews and documentation and then analyzing it using the marketing mix theory or the marketing mix and the linkages to the use of Instagram features. Then test the validity of the data using the source triangulation method.The results of this study state that in promoting the Madiun Umbul Square tourist park using Instagram media in the form of posts, captions, comments, hashtags, tags, likes, followers, mentions, geotagging, Instagram stories, live Instagram and Reels Instagram can support the online promotion process in providing information , and influencing tourists to visit the Madiun Umbul Square tourist park. Based on the results of observations and interviews with several followers, Instagram social media is effective in increasing visitor interest. Evidenced by the statements of followers who know the Madiun Umbul Square tourist park through posts from the @maduiunumbulsquare account. The presence of Instagram social media is effective in increasing visitor interest.